English Teacher's Difficulties In Teaching English at SMPN 1 Kayangan Lombok Utara - Nur Alfilail (Jurnal Ilmiah Wahana Pendidikan, 2022)
As one of importance language, English is included as compulsory subject for junior and senior high school in Indonesia. It aimed to increase the ability of students in communicating using international language. However, in some areas or schools, some teachers face difficulties in teaching English, one of them was teachers in SMPN 1 Kayangan Lombok Utara. This study aimed at investigating the difficulties that were faced by English teachers in SMNPN 1 Kayangan Lombok Utara. This study belonged to qualitative study and purposive sampling was used in taking the sample of the study. In depth interview was used in collecting the data. There were two teachers to be interviewed in this study. The result from the data indicated that there were several difficulties that were faced by teachers in this school namely students’ low of vocabulary mastery, students low motivation, lack of school facilities and conventional method in teaching. From those difficulties, low vocabulary mastery became the main challenge for teachers in teaching English in SMPN 1 Kayangan Lombok Utara.